Seasonal distribution and relative abundance of bottlenose dolphins, Tursiops truncatus, along the US mid-Atlantic Coast - Torres , Leigh G.; McLellan , William A.; Meagher , Erin; Pabst , D. Ann (J. Cetacean Res. Manage., 2023)
In the US mid-Atlantic, multi-disciplinary studies are underway to elucidate the complex stock structure of coastal bottlenose dolphins (Tursiops truncatus), as well as the degree of overlap between coastal and offshore ecotypes. In this study we use geo-referenced data, collected during aerial surveys in 2000-2002, to describe the distribution and relative abundance of bottlenose dolphins along the US midAtlantic coast. Two aerial survey designs were used: (1) onshore/offshore surveys out to 35 n.miles during winter from Georgia to Virginia; and (2) coastal surveys throughout the year along North Carolina (NC). The winter onshore/offshore surveys demonstrated that significantly more bottlenose dolphins occur in Raleigh Bay (between Cape Hatteras and Cape Lookout, NC), than in all other regions. Additionally, in winter most bottlenose dolphins occur in the coastal waters of NC; nearly half of all sightings occurred between the shoreline and 3km from shore. The year-round, coastal surveys demonstrated that this winter distribution pattern is the result of a distinct seasonal increase in the number of dolphins within the coastal waters of NC. Circular statistical analyses demonstrated a strong influence of season on dolphin abundance. Relatively few bottlenose dolphins were observed in late spring, summer, and early autumn, with increased numbers observed during winter. In all seasons but summer, dolphin numbers were highest in Raleigh Bay. Thus, the results of both surveys indicate the importance of the habitat surrounding Cape Hatteras to bottlenose dolphins. Dolphins may preferentially use these waters in response to changes in prey distribution and/or abiotic factors such as water temperature. These results reveal an overall seasonal movement pattern along the US Atlantic coast, which appears to be correlated, at least in part, to water temperature gradients and prey availability. Although the stock identity of dolphins sighted during these aerial surveys could not be ascertained, focused photo-identification efforts, together with enhanced genetic sampling, would provide insights into the movement patterns, and, thus, stock identity, of dolphins in this region.